Similarity Measure between Picture Fuzzy Sets and its applications in Medical Diagnosis: Examining a New Similarity Measure for Picture Fuzzy Sets and its Application in Medical Diagnosis (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Fuzzy sets with intuitionistic properties are more advanced record of the traditional fuzzy sets,which is frequently used in a variety of applications to deal with uncertainty and fuzzy situations. Thedegree of neutrality, which is typically taken into account in medical diagnosis, is one of the crucial andessential components that is not taken into account in IFS. We proposed new similarity measure in thisresearch that may contrast picture Fuzzy Sets(PFSs).The proposed similarity measure on PFSs have beenused to attempt medical diagnosis in this research. It has been discovered that similarity measuresenable the introduction of weights for all symptoms, allowing the patient to be diagnosed directly.